The Systematics of Chlorine, Lithium, and Boron and δ37Cl, δ7Li, and δ11B in the Hydrothermal System of the Yellowstone Plateau Volcanic Field. (20th April 2021) - Cullen, Jeffrey T.; Hurwitz, Shaul; Barnes, Jaime D.; Lassiter, John C.; Penniston‐Dorland, Sarah; Meixner, Anette; Wilckens, Frederike; Kasemann, Simone A.; McCleskey, R. Blaine
Abstract: Chlorine, lithium, and boron are trace elements in rhyolite but are enriched in groundwater flowing through rhyolite because they tend to partition into the fluid phase during high‐temperature fluid‐rock reactions. We present a large data set of major element and δ 37 Cl, δ 7 Li, and δ 11 B compositions of thermal water and rhyolite from Yellowstone Plateau Volcanic Field (YPVF). The Cl/B, Cl/Li, δ 37 Cl (−0.2‰ to +0.7‰), and δ 11 B (−6.2‰ to −5.9‰) values of alkaline‐chloride thermal waters reflect high‐temperature leaching of chlorine, lithium, and boron from rhyolite that has δ 37 Cl and δ 11 B values of +0.1‰ to +0.9‰ and −6.3‰ to −6.2‰, respectively. Chlorine and boron are not reactive, but lithium incorporation into hydrothermal alteration minerals result​s in a large range of Cl/Li, B/Li, and δ 7 Li (−1.2‰ to +3.8‰) values in thermal waters. The relatively large range in δ 7 Li values of thermal waters reflects a large range of values in rhyolite. Large volumes of rhyolite must be leached to account for the chloride, lithium and boron fluxes, implying deep groundwater flow through rhyolite flows and tuffs representing Yellowstone's three eruptive cycles (∼2.1 Ma). Lower Cl/B values in acid‐sulfate waters result from preferential partitioning of boron into the vapor phase and enrichment in the near‐surface water condensate. The Cl/B, Cl/Li, δ 7 Li (−0.3‰ to +2.1‰), and δ 11 B (−8.0‰ to −8.1‰) values of travertine depositing calcium‐carbonate thermal waters which discharge in the northern and southern YPVF suggest that chlorine, lithium, and boron are derived from Mesozoic siliciclastic sediments which contain detrital material from the underlying metamorphic basement. Plain Language Summary: High concentrations of chlorine, lithium, and boron are typically measured in groundwater that chemically react at elevated temperatures with rocks such as rhyolite that have high silica (SiO2 ) concentrations. The elevated concentrations result from the partitioning of these elements into groundwater during chemical reactions. Understanding how the stable isotopes of chlorine, lithium, and boron partition between groundwater and rocks in continental hydrothermal systems can provide guidance for geothermal energy and mineral deposit exploration and for characterizing degassing in active magmatic systems. We present a large data set of major element and stable isotope compositions of thermal waters and rhyolite from the Yellowstone hydrothermal system. Results suggest that the ratios of chlorine to boron and chlorine to lithium and the stable isotope compositions of these three elements mostly reflect the compositions of the rocks with which the hot water reacts. Some lithium is subsequently incorporated into hydrothermal alteration minerals and boron is enriched in vapor when the groundwater boils. Key Points: Cl, Li, and B in alkaline‐chloride thermal water in the Yellowstone Caldera are derived from leaching large volumes of rhyolite Cl and B are not incorporated into hydrothermal alteration minerals, but small amounts of Li are transferred from thermal water to rock In calcium‐carbonate thermal waters which deposit travertine, Cl, Li, and B are probably derived from Mesozoic siliciclastic sediments